Synthesis and characterization of nanosilica particles from Philippine waste rice hull and its potential as an anode raw material in lithium-ion batteries - Mirasol, Emie Salamangkit (College of Engineering, University of the Philippines Diliman, 2015)
The general objective of this study is to produce and characterize nanosilica particles (nSPs) from Philippine waste rice hull (RH) and initially investigate its potential as an anode raw material for Lithium-ion battery (LIB) applications. The experimental processes performed in this study consists of four (4) major stages which are as follows: (1) extraction of bulk silica (SiO2) from raw RH by thermal treatment; (2) synthesis of amorphous nanosilica from bulk SiO2 by acid precipitation method and thermal treatment; (3) characterizations of the synthesized nSPs; and (4) electronic doping of the synthesized amorphous nanosilica (SAnS) and initial electrochemical characterization. All the samples obtained were fully characterized for its microstructural properties. In this study, results showed that amorphous and crystalline SiO2 were successfully obtained from RHs by controlled heat treatment as observed from the CRD patterns and the presence of functional SiO2 groups were confirmed by FITR. Likewise, morphology and compositions of the obtained SiO2 from the rice hull ashses (RHAs) by SEM-EDS revealed that agglomerated particles of wide range of sizes and some metallic impurities like potassium (K) were present. On the other hand, amorphous nanosilica (AnS) of ~ 95 % purity in agglomerated form were successfully synthesized by acid precipitation method and fully characterized using XRD, FTIR, SEM-EDS, PSA, and TEM analyses. Leaching RHAs with 1M HCl efficiently removed the K elements. The SAnS from purified rice hull as (PRHA) was successfully doped with iron (Fe) with the presence of some carbon. EDS elemental mapping revealed a homogeneous distribution of the Si, O, C, and Fe elements. In addition, the initial investigation on the electrochemical performance of the 5 mol % Fe-doped AnS from PRHA revealed a specific capacity of 1232 mAh/g upon lithiation; however, only 8 mAh/g upon delithiation. The resulting lithiation capacity is almost four time higher as compared to commercial graphite anode which indicates that the nanosilica obtained from the Philippine waste RH can be a potential anode material for LIB applications.